The Influence of In Store Stimuli and Sales Person on Consumer Impulsive Buying in Alfamart Area, Ngaliyan District, Semarang - Gema Taufik Habibie; Saptianing - Saptianing; Endang - Sulistiyani (Admisi dan Bisnis, 2019)
The purpose of this study is to determine the effect of variables in store stimuli and sales person on impulsive buying consumers on Alfamart area district of Ngaliyan Semarang. In 2003 and 2011, Nielsen conducted a survey of Indonesian modern retail buyers tend to buy something that was not planned. Average monthly sales from January to April 2017, Alfamart retail in the Ngaliyan area of Semarang largely has not met the targets set by the company. Technique of collecting data was done through distributing questionnaires in Alfamart area of Ngaliyan Sub-district and interviewed to company management regarding stimulus that has been created and literature studyies as well. Data analysis techniques used were the validity test, reliability test, multiple linear regression test with the help of SPSS software version22. The result of regression positive influence on consumer impulsive buying, and the influence of sales person was greater that in store stimuli. The result of analysis showed that all variable of this research were positive influence on  consumer impulsive buying. Coefficient determination is 0,288, it means that 28,8% of impulsive buying consumer could be explained by in store stimuli and sales person